Effects of interval training on health-related fitness among sedentary university students - Ming, Carol Lau Kho (Universiti Sains Malaysia, 2017)
The present study compared the effect of interval training on health-related fitness and its effect over time. Responses in body composition, cardiorespiratory endurance, muscular strength, muscular endurance and flexibility was examined. Thirty-seven healthy, sedentary female participants from Universiti Sains Malaysia Health Campus were recruited in this study. Interval training consisted of 18 sessions were completed over six weeks. Results indicated significantly improved cardiorespiratory endurance, muscular strength, muscular endurance and flexibility after intervention. It is concluded that interval training can be used as an alternative for endurance training for untrained population.